Модель управления товарными запасами в условиях случайного спроса - Рыбников, М.С.; Семенова, Ю.А. (Культура народов Причерноморья, 2014)
В статье представлена математическая модель управления запасами торгового
предприятия со стохастическим характером спроса. Указанная модель является многоэтапной и
многопродуктовой. Один и тот же товар может быть заказан у нескольких поставщиков, имеющих
различные цены и условия доставки. Результатом применения представленной модели управления
запасами является получение оперативного плана закупок, позволяющего минимизировать издержки. У статті представлена математична модель управління запасами торгового підприємства
зі стохастичним характером попиту. Зазначена модель є багатоетапної і багатопродуктової. Один і
той же товар може бути замовлений у кількох постачальників, що мають різні ціни та умови
доставки. Результатом застосування представленої моделі управління запасами є отримання
оперативного плану закупівель, що дозволяє мінімізувати витрати. In this work towards the development of analysis tools a mathematical model of inventory
management in the conditions of uncertainty associated with stochasticity demand is developed. Implementation
of the model and software module constructed on the basis of it will improve the system of inventory
management, reduce the time for processing applications agents reduce the risk of biased order that will
increase the competitiveness and efficiency of the whole enterprise. In operation processes of the majority of
commercial enterprises there are problems of inventory control. The main reason that force the company to keep
stocks is the need to meet demand. However a study and a number of problems associated with inventory
management and distribution especially in systems with random demand and application for this economic and
mathematical modeling are still relevant and that led to the choice of the research topic. In this paper the
inventory control model of commodities allocated for instance from group A in the ABC / XYZ – analysis or the
frequency of sales in the frequency analysis is researched. These tasks are respectively the prerogatives of
logistics and inventory logistics procurement. The logistics goal is to minimize inventory costs and to reduce
inventory, goal of logistics procurement is to reduce the unit cost of the order, which was associated with
increased order volume. In one case, there is a tendency to reduce the amount of inventory, in other – to
increase. The purpose of this article is to combine these logistics tasks into a coherent whole and to construct the
corresponding economic–mathematical model. All existing models of inventory control can be divided into
single–stage and multi–stage models. In the multi–stage model of inventory management order placing decision
is made on each stage. In multi–stage models must be taken into account the money present value. Limitation to
the possible application of the constructed model of inventory management is the inability to place an order for
the supply of a particular product from multiple vendors simultaneously on the same stage. The presented model
will optimize inventory management costs thereby increasing profits. Accounting conditions of supply while
problem setting (cost of the order placing and deadline) for various commodities by several suppliers reduces
the number of stages of decision–making and increases the efficiency of the decision making process .